The Influence of Transformational Leadership and Organizational Justice on Innovative Work Behavior: the Mediating Role of Psychological Capital and Knowledge Sharing - Adrian Ajrurrahman; Elok Savitri Pusparini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Innovative work behavior is every Civil Servant (PNS) must have to encourage individuals to produce new thoughts, methods and work processes that can be used to increase organizational efficiency and effectiveness. Research on innovative work behavior for civil servants still needs to be widely researched, especially in developing countries. For this reason, this research aims to identify the influence of transformational leadership, organizational justice, psychological capital, and knowledge sharing on innovative work behavior. Data collection was carried out in a single cross-sectional using purposive sampling. The research sample was obtained from Civil Servants who work at State Institutions of Government in Indonesia. The data was processed using Structural Equation Modeling (SEM) with the Partial Least Square SEM (PLS-SEM) with 385 respondents. The results of this study prove a positive and significant relationship between transformational leadership, organizational justice, psychological capital, and knowledge sharing on innovative work behavior. In addition, empirical results show that psychological capital and knowledge sharing can partially mediate the relationship between transformational leadership and organizational justice on innovative work behavior. State Institutions of Government are expected to receive input and suggestions regarding the implementation of leadership and organizational policies so that employees have a positive psychology and a desire to share knowledge and skills so that they can create new ideas as organizational innovations.